Indicadores morfométricos: uma ferramenta no diagnóstico da vulnerabilidade ambiental - Costa, Renata Cristina Araujo [UNESP] (2015)
This study attempts to propose environmental indicators of public poli-cies from the spatial distribution of morphometric characteristics and its relation to areas in environmental conflict and vulnerability of environmental deterioration. As a result of this analysis hydrological compartments were considered as evaluation units, and in them were determined the morphometric parameters as: area, perime-ter, length of the drainage network, drainage density, number of channels, frequency of rivers and relief to evaluate the natural erosion, using the land use conflict tech-nique and the vulnerability of the watershed. The morphometric parameters were submitted to descriptive and exploratory multivariate statistical analysis. The autocor-relation between the morphometric parameters and the similarity between the hydro-logical compartments were evaluated. The spatial distribution of the values of the number of channels (Nt) has generated environmental physical indicators which enbled the areas of differentiation. Identifying the use of conflict zones is as important tool to propose plans of management and conservation of land use, aiding in the making of public officials decision. The vulnerability map of the watershed for the multicriteria analysis (MCA) indicated morphometric standards of the most vulnerable areas to natural soil erosion and consequently greater environmental fragility. The high correlation between the vulnerability of the basin validates the theory of the risk of erosion and environmental deterioration and can be used as a tool and environ-mental vulnerability indicator in watersheds. The environmental evaluation of Jabuti-cabal watershed indicated that the watershed has low impact and of little signifi-cance, but the degree of average of the real deterioration determined by the matrix by Leopold-Rocha shows that the environment is deteriorated, since the obtained value is above the acceptable rate and should be ...